Assessment of Chronic Postsurgical Pain Knowledge Among Surgical Nurses in a Turkish University Hospital - Dogan, Aysel; Dogan, Runida; Gunes, Dilek; Bagci, Nazlican (Wiley, 2025)
Objective: Chronic postsurgical pain (CPSP) is a significant yet often underrecognized complication following surgical procedures, impacting patients' quality of life. Surgical nurses play a crucial role in postoperative care and pain management, making their knowledge of CPSP essential for improving patient outcomes. The aim of the study was to assess CPSP knowledge among surgical nurses in a Turkish University Hospital. Methods: This descriptive cross-sectional study included a total of 175 nurses. Data were collected from nurses employed in the surgical units of & Idot;n & ouml;n & uuml; University hospital between May 15 and June 15, 2023. Personal information and knowledge-level forms created by the researchers were used for data collection. IBM SPSS Statistics v.25 was used for the statistical analysis. Results: The mean CPSP knowledge score of the nurses working in surgical clinics was 9.26 +/- 1.40 (min. = 0, max. = 12) and 75.4% of them had sufficient knowledge. Surgical nurses' knowledge level of CPSP was influenced by their education level (p <= 0.001) and total duration of employment in the surgical department (p = 0.002). Conclusions: Although most surgical nurses had sufficient CPSP knowledge, gaps remained, particularly among those with lower education levels and less experience. Targeted training programs and continuous professional development initiatives are recommended to enhance CPSP awareness and improve postoperative pain management practices.
Keywords: chronic postsurgical pain; knowledge; nurse; surgical clinics